Changes in Demand and Supply of the Crude Oil Market During the COVID-19 Pandemic and its Effects on the Natural Gas Market - Indupurnahayu, Indupurnahayu; Setiawan, Edhie Budi; Agusinta, Lira; Suryawan, Ryan Firdiansyah; Ricardianto, Prasadja; Sari, Mustika; Mulyono, Sri; Sakti, Reza Fauzi Jaya (International Journal of Energy Economics and Policy, 2021)
As a source of revenue for the state budget and a source of energy (particularly fuel) to drive various sectors of life, the oil and gas industry plays an important role in the Indonesian economy. The purpose of this study is to analyse the effect of crude oil prices on natural gas during the Covid19 Pandemic in Indonesia. The research method used is an explanatory method using the real price decomposition of crude oil introduced recently by Kilian (2009). This study develops four variables for the oil and natural gas market through a structural vector autoregressive model (SVAR). Based on the results of the analysis, hence some evidence is found that the crude oil market affects the natural gas market in Indonesia through a combination of changes in demand and not through changes in oil supply during the Covid-19 pandemic. The uncertainty of oil supply due to the Covid-19 pandemic has made the oil market shift to the natural gas market and increased the price of natural gas as the main substitute for oil. Meanwhile, changes in demand in Indonesia during the Covid19 Pandemic affected crude oil and gas prices, causing similar fluctuations in oil and gas prices. Keywords: Crude Oil Prices, Natural Gas Prices, Demand, and Supply JEL Classifications: P41, P28, P43 DOI: https://doi.org/10.32479/ijeep.10671